Uji Anti Jamur Ekstrak Buah Mengkudu (Morinda citrifolia L.) - Ririen Hardani; I Kadek Adi Krisna; Baharuddin Hamzah; Muhammad Fakhrul Hardani (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
Noni is a plant that has the potential to be used as traditional medicinal ingredients. This study aims to determine the inhibition of noni extracts (Morinda citrifolia L.) in inhibiting the growth of the fungus Candida albicans. This type of research is experimental. A total of 150 grams of dried noni fruit that has been mashed, macerated with three different types of solvents namely aquades, acetone and n-hexane to obtain thick extract. Preparation of the fungus suspension was Candida albicans made by mixing the media Nutrient Broth with 5 ose test fungus that were equated with turbidity of a standard MC. Farland. The fungus suspension made was implanted on the Sabouroud Dextrose agar to solidify and divided into 7 sterile petri dishes. Testing the inhibition of fungi using the method of wells. Each cup is made of 1 hole diameter of 3 cm in the center. Tests were carried out by adding non-solvent aquades fruit extract into the 1 cup, acetone noni fruit extract into the cup 2, n-hexane solvent noni fruit extract into the cup 3, for 3 other plates added with three solvents as negative control, while for 1 cup added to the cup fungal infection drug is nystatin as a positive control, each as much as 1 mL. Measurement data were analyzed using the formula of the percentage of inhibition. Inhibitory power of noni fruit extract using distilled water is 3.55%, noni fruit extract using acetone solvent is 50.15%, noni fruit extract using n-hexane solvent that is equal to 38.83%. negative control of aquades, acetone and n-hexane solvent has no inhibitory power while positive control of nystatin is 9.73%. Noni fruit extract using acetone solvent has the strongest inhibitory ability. It can be concluded that the noni fruit extract has fungal inhibitory effect on the growth of the fungus Candida albicans